A new methodical approach based on Compton scattering and XRF: quantitative analysis of CO2 and loss on ignition in quicklime. Issue 2 (20th May 2015) - Inoue, Minoru; Yamada, Yasujiro; Kitamura, Mao; Gotoh, Norifumi; Kawahara, Naoki; Mantler, Michael
<x content-type="archive" xml:space="preserve">Abstract</x> The authors present and discuss a method for simultaneous quantitative analysis of total loss on ignition (LOI) (CO2 + H2O) and CO2 content separate from the LOI, in an industrial environment of quicklime production. Total LOI is determined by the Compton scattered RhKα tube radiation which is used directly in the calibration equation. The resulting calibration curve for LOI, including matrix correction shows an accuracy of 0.15 mass%. The carbon content (CO2) is distinguished from total LOI by measuring CKα radiation, which is possible with the required accuracy by employing a new multilayer analyzer with greatly improved background characteristics. The method aims at high reliability and sample throughput and at becoming a less time-consuming alternative to the conventional method of LOI determination by weighing sequences before and after "ignition" at 1050 °C.